Trypanosoma cruzi infection in the wild Chagas disease vector, Mepraia spinolai: Parasitic load, discrete typing units, and blood meal sources - Saavedra, Miguel; Bacigalupo, Antonella; Barrera, María Victoria; Vergara, María J.; Álvarez Duhart, Bárbara.; Muñoz San Martín, Catalina.; Solís, Rigoberto; Cattan, Pedro E. (Elsevier B.V., 2022)
Background: Mepraia spinolai, a wild vector of Trypanosoma cruzi in Chile, is an abundant triatomine species that is frequently infected by the parasite that causes Chagas disease. The aim of this study was to determine if the parasitic load of T. cruzi in M. spinolai is related to its blood meal source and the infecting DTUs of T. cruzi. Methods: The vector was captured in rural areas. In the laboratory, DNA was extracted from its abdomen and T. cruzi was quantified using qPCR. Real time PCR assays for four T. cruzi DTUs were performed. Blood meal sources were identified by real-time PCR amplification of vertebrate cytochrome b gene sequences coupled with high resolution melting (HRM). Results: Trypanosoma cruzi was detected in 735 M. spinolai; in 484 we identified one blood meal source, corre- sponding to human, sylvatic, and domestic species. From these, in 224 we were able to discriminate the infecting DTU. When comparing the parasitic loads between the unique blood meal sources, no significant differences were found, but infections with more than one DTU showed higher parasitic loads than single infections. DTU TcI was detected in a high proportion of the samples. Conclusions: Higher parasitic loads are related to a greater number of T. cruzi DTUs infecting M. spinolai, and this triatomine seems to have a wide span of vertebrate species in its diet.
Keywords: DTUs; Parasite load; Chagas' disease; Trypanosoma cruzi; Kissing-bug; Triatominae